Boosting the charge transfer of Li2TiSiO5 using nitrogen-doped carbon nanofibers: towards high-rate, long-life lithium-ion batteries. Issue 38 (23rd September 2020) - Liu, Junfang; Su, Die; Liu, Li; Liu, Zhixiao; Nie, Su; Zhang, Yue; Xia, Jing; Deng, Huiqiu; Wang, Xianyou
Abstract : The nitrogen-doped carbon encapsulated Li2 TiSiO5 (the insulator for transferring electrons by first-principles calculation) nanofibers were fabricated. And unexpectedly, it can boost the charge transfer effectively. Abstract : Li2 TiSiO5 (LTSO) has a theoretical specific capacity of up to 315 mA h g −1 with a suitable working potential (0.28 V vs. Li/Li + ). However, the electronic structure of Li2 TiSiO5 is firstly investigated by theoretical calculation based on the first-principles approach, and the results demonstrate that Li2 TiSiO5 acts as the insulator for transferring electrons. Therefore, the framework with better conductivity is very essential for Li2 TiSiO5 to enhance the charge transfer kinetics. Nitrogen-doped carbon encapsulated Li2 TiSiO5 nanofibers (LTSO/NDC nanofibers) are obtained by using carbamide as a nitrogen source through an electrospinning technique. The nitrogen-doped carbon matrix with high electronic conductivity improves the electrochemical properties of LTSO significantly. The diffusion coefficient of lithium ions ( D Li + ) is greatly improved by manual calculation. The LTSO/NDC nanofiber electrode can deliver 371.7 mA h g −1 at 0.1 A g −1 and 361.1 mA h g −1 at 0.2 A g −1, and also shows a comparable cycle performance which could endure a long cycle over 800 cycles at 0.5 A g −1 almost without capacity decay. Hence, the LTSO/NDC nanofiber anode with a high rate and a long life provides a new direction for the realization of LTSO-based compounds in lithium ion batteries.